Diurnal cycle of precipitation in Estonia - Regina Alber; Jaak Jaagus; Peeter Oja (Estonian Journal of Earth Sciences, 2015)
The diurnal cycle of precipitation in Estonia during the warm period (from April to October) is analysed separately at continental and coastal stations. The results were obtained using hourly data from the automated gauges at 13 stations in 2003–2013 as well as from the pluviographic records at 10 stations in 1991–2003. The diurnal cycle is approximated using the second-order trigonometric polynomial. A clear diurnal cycle of precipitation with the maximum in the afternoon and evening (13–19 EET – East European Time), and the minimum at night and in the morning (22–11 EET) was revealed at the continental stations of Estonia. The daily amplitude was the highest in summer and much lower in spring and autumn. The highest monthly mean daily amplitudes up to 7 mm were observed in June and July. The diurnal cycle of precipitation was much weaker at the coastal stations without clear maxima and minima and with lower amplitudes. In autumn, the coastal stations showed clearer and bimodal maxima in the early morning and in the evening. The diurnal distribution of precipitation is quite stable, which is confirmed by the high similarity of the curves characterizing these two periods.